PROSPECTS OF ITALEXIT IN THE CONTEXT OF RISKS OF STRENGTHENING DISINTEGRATION PROCESSES IN EUROPE - Геба, Г. І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2021)
The risks of Italy's withdrawal from the European Union (Italexit) are analyzed. Italy has one of the most powerful economies in the European Union and a great political influence on the processes in the EU. Therefore, the possible exit of this country from the Union could have catastrophic economic and political consequences for the future of European integration. The probability of the threat of the so-called Italexit, which has been discussed by the Italian politicians for a long time, is researched. In addition, the ways and possibilities of avoiding the threat of Italexit, as well as strengthening European solidarity despite the development of disintegration processes in Europe in general and in Italy in particular, are discovered. The probability of Italexit is defined as low, but some negative trends that may increase the risks of Italy's exit from the EU in the future are outlined. The growing sentiments of euroscepticism in Italy and their impact on the country's foreign policy and on relations between Italy and the EU's central institutions in Brussels are observed. The most influential parties of Eurosceptics and right-wing populists and their activities in the Italian parliament and government are considered. The prospects for further activities of Eurosceptic parties and their potential impact on the policy of Italy and the EU are forecasted. It is proved that Italian Eurosceptics are potentially the most dangerous in Europe because of their popularity not only at the national but also at the European level, their ability to unite right-wing radical parties from other European countries, their ambitions to occupy key positions in the European Commission and their active ties with Russia. The possible ways to avoid the most catastrophic scenarios of Italy's exit from the EU are analyzed.